2016
DOI: 10.1016/j.jamda.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Delirium Superimposed on Dementia: Evaluation of the Diagnostic Performance of the Richmond Agitation and Sedation Scale

Abstract: Objectives Delirium disproportionately affects patients with dementia and is associated with adverse outcomes. The diagnosis of delirium superimposed on dementia (DSD), however, can be challenging due to several factors including the absence of caregivers or the severity of pre-existing cognitive impairment. Altered level of consciousness has been advocated as a possible useful indicator of delirium in this population. Here we evaluated the performance of the Richmond Agitation and Sedation Scale (RASS) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 33 publications
(51 reference statements)
0
29
0
7
Order By: Relevance
“…The Modified Richmond Agitation and Sedation Scale (mRASS), which measures arousal, sedation and level of consciousness, has been advocated as a screening tool for delirium. However, the mRASS has a low sensitivity of 64% to70%, 42, 43 and the usefulness of the scale depends on the prevalence of decreased mental status in the population. In settings with high prevalence of sedation and depressed sensorium, such as the postoperative recovery room and ICU, this approach may be valuable; however, routine use of the mRASS is not recommended outside of these settings, since many cases of delirium will be missed.…”
Section: Resultsmentioning
confidence: 99%
“…The Modified Richmond Agitation and Sedation Scale (mRASS), which measures arousal, sedation and level of consciousness, has been advocated as a screening tool for delirium. However, the mRASS has a low sensitivity of 64% to70%, 42, 43 and the usefulness of the scale depends on the prevalence of decreased mental status in the population. In settings with high prevalence of sedation and depressed sensorium, such as the postoperative recovery room and ICU, this approach may be valuable; however, routine use of the mRASS is not recommended outside of these settings, since many cases of delirium will be missed.…”
Section: Resultsmentioning
confidence: 99%
“…[42, 43] In the ICU, delirium evaluation in the context of dementia requires an accurate evaluation of the level of arousal. Acknowledging the current limitations of tools to assess DSD, it is still imperative to screen for DSD, using standard tools such as the CAM-ICU and ICDSC.…”
Section: What Are the Major Recent Advances In Delirium Research And mentioning
confidence: 99%
“…Acknowledging the current limitations of tools to assess DSD, it is still imperative to screen for DSD, using standard tools such as the CAM-ICU and ICDSC. [43]…”
Section: What Are the Major Recent Advances In Delirium Research And mentioning
confidence: 99%
“…42 Both the RASS and the m-RASS are ultra-brief assessments of the level of consciousness, and recent studies have suggested that they have high specificity for delirium in geriatrics wards, emergency departments, 37,42,43 and specifically in patients with dementia. 44 …”
Section: The Challenge Of Neuropsychological Assessment Of Delirium Imentioning
confidence: 99%